Measuring Concentration Risk : A Partial Portfolio Approach - Grippa, Pierpaolo (IMF Working Papers; Working Paper ;, 2016)
Concentration risk is an important feature of many banking sectors, especially in emerging and small economies. Under the Basel Framework, Pillar 1 capital requirements for credit risk do not cover concentration risk, and those calculated under the Internal Ratings Based (IRB) approach explicitly exclude it. Banks are expected to compensate for this by autonomously estimating and setting aside appropriate capital buffers, which supervisors are required to assess and possibly challenge within the Pillar 2 process. Inadequate reflection of this risk can lead to insufficient capital levels even when the capital ratios seem high. We propose a flexible technique, based on a combination of 'full' credit portfolio modeling and asymptotic results, to calculate capital requirements for name and sector concentration risk in banks' portfolios. The proposed approach lends itself to be used in bilateral surveillance, as a potential area for technical assistance on banking supervision, and as a policy tool to gauge the degree of concentration risk in different banking systems.